2011
DOI: 10.5533/2177-8264-201123107
|View full text |Cite
|
Sign up to set email alerts
|

Mulheres Portadoras de lesões Precursoras do câncer do colo do Útero e hPV: descrição do Perfil socioeconôMico e deMográfico

Abstract: INTRODUÇÃOAs lesões precursoras do câncer do colo do útero (LPCCU) são entendidas como alterações cervicais pré-malignas, que constituem uma série de modificações no epitélio original e, quando não tratadas, podem evoluir para o câncer cervical 1 . A gravidade deste tipo de câncer está associada à infecção pelo papilomavírus humano em 99% dos casos. Desta maneira, entender a diversidade de fatores socioeconômicos e demográficos das mulheres portadoras de neoplasias intraepiteliais cervicais é fundamental, pois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 13 publications
(16 reference statements)
1
8
0
8
Order By: Relevance
“…A predominance of non-white women (91.75%) was found, approaching the results of Carvalho and Queiroz 16 and Ribeiro et al, 17 who found a frequency of 63.3% and 82.1%, respectively, of women of non-white color in the existence of the diagnosis. However, in contrast to these results, Carmo and Luiz 18 showed a predominance of the white race (55.5%) in women diagnosed with cervical cancer and treated at the National Cancer Institute, Rio de Janeiro, justifying the use of race/color as a social marker more related to envi- ronmental factors, contributing to the lack of access to cytopathological exams.…”
Section: Discussionsupporting
confidence: 52%
“…A predominance of non-white women (91.75%) was found, approaching the results of Carvalho and Queiroz 16 and Ribeiro et al, 17 who found a frequency of 63.3% and 82.1%, respectively, of women of non-white color in the existence of the diagnosis. However, in contrast to these results, Carmo and Luiz 18 showed a predominance of the white race (55.5%) in women diagnosed with cervical cancer and treated at the National Cancer Institute, Rio de Janeiro, justifying the use of race/color as a social marker more related to envi- ronmental factors, contributing to the lack of access to cytopathological exams.…”
Section: Discussionsupporting
confidence: 52%
“…Education is a determining factor in social vulnerability. Knowledge mediates attitudes that will benefit or not the risk perception regarding the cervical cancer precursor lesions ( 18 ) . Access to healthcare services and adherence to the HIV/AIDS treatment are also mediated by education, which impacts on the comprehension of the therapy, due to difficulties in the interpretation of the information provided by the health team and in the recognition of the importance of performing the treatment correctly ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“… 6 - 8 This discrepancy is possibly due to the diversity of the source of data. The predominance of condyloma acuminatum was in agreement with the findings by Carvalho and Queiroz 8 , but differed from the findings by Virgili et al . 6 and Farias et al .…”
mentioning
confidence: 99%